Monogenic free inverse semigroups and partial automorphisms of regular rooted trees - E. Kochubinska; A. Oliynyk (Математичні Студії, 2024)
For a one-to-one partial mapping on an infinite set, we present a criterion in terms of its cycle-chain decomposition that the inverse subsemigroup generated by this mapping is monogenic free inverse.